An Efficient, Lung-Targeted, Drug-Delivery System To Treat Asthma Via Microparticles - SreeHarsha, Nagaraja (Drug Des Devel Ther, 2019)
BACKGROUND: Chronic diseases such as diabetes, asthma, and heart disease are the leading causes of death in developing countries. Public health plays an important role in preventing such diseases to improve individuals’ quality of life. Conventional dosage schemes used in public health to cure various diseases generally lead to undesirable side effects and renders the overall treatment ineffective. For example, a required concentration of drug cannot reach the lungs using conventional methods to cure asthma. Microspheres have emerged as a confirmed drug-delivery system to cure asthma. METHOD: In this paper, a salbutamol-loaded poly lactic acid-co-glycolic acid-polyethylene glycol (PLGA-PEG) microsphere (SPP)-based formulation was prepared using a Buchi B-90 nanospray drier. Face-centered central composite design (CCD) was applied to optimize the spray-drying process. RESULTS: The drug content and product yield were found to be 72%±0.8% and 86%±0.4%, respectively; drug release (91.1%) peaked for up to 12 hrs in vitro. Microspheres obtained from the spray dryer were found to be shriveled. The experiments were carried out and verified using various groups of rabbits. In our study, the particle size (8.24 µm) was observed to be an essential parameter for drug delivery. The in vivo results indicated that the targeting efficacy and drug concentration in the lung was higher with the salbutamol-loaded PLGA-PEG SPP formulation (1,410.1±10.11 µg/g, 15 mins), as compared to the conventional formulation (92±0.56 µg/g, 10 min). The final product was stable under 5°C±2°C, 25°C±2°C, and 40°C±2°C/75%±5% relative humidity. In addition, these co-polymers have a good safety profile, as determined by testing on human alveolar basal epithelium A549 cell lines. CONCLUSION: Our results prove that microspheres are an alternative drug-delivery system for lung-targeted asthma treatments used in public health.